Feminist destinations and further essays on Virginia Woolf - Bowlby, Rachel, 1957- (Edinburgh University Press, 1997)
Feminist Destinations now appears with five essays which look at Woolf in a number of new frames - as a woman essayist; as a city writer and critic of modern culture; as a writer on love. Rachel Bowlby shows, with inimitable critical panache, how it is that Woolf's writing, in its many forms and fashions, continues to provide rich matter for thinking about the histories and futures of women, writing and culture.